Clinicopathological characteristics including BRAF V600E mutation status and PET/CT findings in papillary thyroid carcinoma. (18th April 2017) - Choi, Eun Kyoung; Chong, Ari; Ha, Jung‐Min; Jung, Chan Kwon; O, Joo Hyun; Kim, Sung Hoon
Summary: Objective: We assessed the associations between FDG uptake in primary papillary thyroid carcinomas (PTCs) and clinicopathological features, including the BRAF V600E mutation, using quantitative and qualitative analyses of preoperative PET/CT data. Design and Patients: This was a retrospective review of 106 patients with PTC who underwent PET/CT scans between February 2009 and January 2011 before undergoing total thyroidectomy. Data collected from surgical specimens were compared with FDG uptake in the primary tumour using quantitative and qualitative analyses of preoperative PET/CT data. Clinicopathological data included the primary tumour size, subtype, capsular invasion, extrathyroid extension, multifocality, BRAF V600E mutation status, lymph node metastasis and distant metastasis. Results: The SUVmax of the primary tumour was significantly higher in patients with a primary tumour >1 cm, extrathyroid extension or the BRAF V600E mutation than in patients without these features ( P <.001, .049 and <.001). Univariate analyses showed that primary tumour size, extrathyroid extension and BRAF V600E mutation status were associated with the SUVmax of the PTC. Multivariate analysis indicated that primary tumour size and the BRAF V600E mutation were associated with the SUVmax of the PTC. In a visual assessment, the primary tumour size was larger in FDG‐avid than in non‐FDG‐avid PTCs ( P <.001). There was no significant difference in the presence of multifocality, thyroid capsular invasion, extrathyroid extension, BRAF V600E mutation, lymph node metastasis or distant metastasis between FDG‐avid and non‐FDG‐avid PTCs. Conclusions: Primary tumour size and the BRAF V600E mutation are significant factors associated with the SUVmax on preoperative PET/CT in patients with PTC.